Character and the supernatural in Shakespeare and Achebe - Usongo, Kenneth (New York, NY : Routledge, 2021)
"Through mainly a New Historicist critical approach, this book explores how Shakespeare and Achebe employ supernatural devices such as prophecies, dreams, gods/goddesses, beliefs, and divinations to create complex characters"--
Contextualizing Shakespeare and Achebe. Differences between Shakespeare and Achebe -- The term supernatural. Early western embodiments of the supernatural -- Igbo embodiments of the supernatural -- Literary manifestations of the supernatural -- Shakespeare and the supernatural. King Lear -- Macbeth -- Julius Caesar -- Hamlet -- Othello -- Achebe and the supernatural -- The supernatural and character -- The supernatural as premonitory -- The supernatural and morality -- Shakespeare's and Achebe's use of the supernatural -- Impact of the supernatural on the protagonists -- The supernatural as prolepsis and moral implications.
OCLC-licensed vendor bibliographic record.
Keywords: Shakespeare, William, -- 1564-1616 -- Characters; Achebe, Chinua -- Characters; Supernatural in literature; LITERARY CRITICISM / Shakespeare; LITERARY CRITICISM / African